Achieving zT > 1 in Inexpensive Zintl Phase Ca9Zn4+xSb9 by Phase Boundary Mapping. (29th March 2017) - Ohno, Saneyuki; Aydemir, Umut; Amsler, Maximilian; Pöhls, Jan‐Hendrik; Chanakian, Sevan; Zevalkink, Alex; White, Mary Anne; Bux, Sabah K.; Wolverton, Chris; Snyder, G. Jeffrey
Abstract : Complex multinary compounds (ternary, quaternary, and higher) offer countless opportunities for discovering new semiconductors for applications such as photovoltaics and thermoelectrics. However, controlling doping has been a major challenge in complex semiconductors as there are many possibilities for charged intrinsic defects (e.g., vacancies, interstitials, antisite defects) whose energy depends on competing impurity phases. Even in compounds with no apparent deviation from a stoichiometric nominal composition, such defects commonly lead to free carrier concentrations in excess of 10 20 cm −3 . Nevertheless, by slightly altering the nominal composition, these defect concentrations can be tuned with small variation of the chemical potentials (composition) of each element. While the variation of chemical composition is undetectable, it is shown that the changes can be inferred by mapping (in nominal composition space) the boundaries where different competing impurity phases form. In the inexpensive Zintl compound Ca9 Zn4+ x Sb9, the carrier concentrations can be finely tuned within three different three‐phase regions by altering the nominal composition ( x = 0.2–0.8), enabling the doubling of thermoelectric performance (zT). Because of the low thermal conductivity, the zT can reach as high as 1.1 at 875 K, which is one of the highest among the earth abundant p‐type thermoelectrics with no ion conducting. Abstract : The charge carrier concentration of the inexpensive multinary Zintl semiconductor Ca9 Zn4+ x Sb9 can be finely tuned within three different three‐phase regions via phase boundary mapping by slightly altering the nominal composition ( x = 0.2–0.8), enabling the optimization of thermoelectric performance (zT = 1.1 at 875 K). This is one of the highest among the inexpensive p‐type thermoelectrics with no ion conduction.